Locations of knowledge in medieval and early modern Europe: esoteric discourse and Western identities - Stuckrad, Kocku von (Brill's studies in intellectual history, 2010)
Esoteric discourse and the European history of religion -- Europe and the Christendom narrative -- From singularization to pluralism -- The secularization theory revisited -- Christian Occident? -- The two-fold pluralism -- The polemical construction of tradition -- The construction of Prisca Theologia -- Genealogies of wisdom -- Jewish perspectives -- Beyond tradition -- Conceptualizing the study of esoteric discourse -- Approaches to esotericism -- Secrecy as social capital -- Discourses of perfect knowledge -- Shared passions -- The secrets of experience : wisdom beyond demonstration -- Neoplatonism and theurgy in late antiquity -- Experiential knowledge in Suhrawardi's illuminationist philosophy -- The secrets of texts : esoteric hermeneutics -- The readability of the cosmos : Europe's obsession with words -- The textile of the divine in early Kabbalah -- Linguistic ontologies in Christian Kabbalah -- Humanistic philology : universal languages and the quest for the Ursprache -- The secrets of time : astrology and sacred history -- Critical response to ancient traditions : medieval Arabic astrology -- Sharing Muslim knowledge : Christian astrology -- Interferences -- Scientific encounters -- "Occult sciences" : the science-religion divide revisited -- John Dee : a scholar gone mad? -- Natural philosophy in an apocalyptic age -- Visual seductions -- The problem of "Renaissance paganism" -- Image acts and visual culture -- The presence of images as visual practice -- Political consideration -- Johann Heinrich Alsted : hermeticism and universal reform -- Perfect knowledge in the "circle of learning" : Alsted's encyclopaedia -- Conclusion: locations of knowledge -- Writing histories, narrating pasts -- Esoteric discourse and Western identities